A stylometric analysis of two sentimental letters by Albert Einstein and Simón Bolívar - Isea, Raul (Journal of Language Research, 2023)
On social networks often circulate emotional letters from various authors that appear after their death. The supposed letter Albert Einstein wrote to his daughter Lieserl and the letter Simon Bolivar wrote to his cousin Fanny are two examples. A Python-developed tool is used to do a stylometric study to determine whether these authors were. The language styles of Einstein and Bolivar were described using eight and six letters, respectively. The results show that they never wrote these letters.
Keywords: Albert Einstein; Simón Bolívar; Stylometric; Linguistic footprint; Letter.